A comparative review and analysis of tentative ecological quality objectives (EcoQOs) for protection of marine environments in Korea and China. (November 2018) - Khim, Jong Seong; Hong, Seongjin; Yoon, Seo Joon; Nam, Jungho; Ryu, Jongseong; Kang, Seong-Gil
Abstract: Ecological quality objectives (EcoQOs), as tools for implementing ecosystem approach, have long been acknowledged to protect the marine ecosystems and fisheries in regional seas through joint efforts by surrounding countries over the past decade. The present review analyzed the best available meta-data relating to the five ecosystem elements that were recently proposed by the Northwest Pacific Action Plan to evaluate the current status of coastal ecosystem health in marine environment of the Yellow Sea. We suggested the six tentative EcoQOs among five ecological quality elements including: 1) biological and habitat diversity; 2) invasive species; 3) eutrophication; 4) pollutants; and 5) marine litters. Environmental status was assessed, depending on the EcoQOs targets, by comparison to the world average values, existing environmental standards, or reported values of other regional seas. Results of analysis revealed that among the six tentative EcoQOs, two target objectives to marine biodiversity and concentrations of nutrients (viz., DIN and DIP) were met towards good environmental status. Whilst, three EcoQOs relating to hypoxia and red-tide, pollutants (persistent toxic substances and metals), and marine litters (including microplastics) did not meet and one relating to invasive species could not be judged due to insufficient data sets. The biggest weak point for developing suitable EcoQOs and assessing status of ecosystem health could be insufficient meta-data sets available and/or discrepancy in methodological details cross the data-sets or between the two targeted countries. Thus, the cooperation of neighboring countries, viz., Korea and China for the Yellow Sea, is necessary for the ecosystem based management of our regional sea in the future. Overall, this first time review for the assessment of target tentative EcoQOs in the Yellow Sea region encompassing coasts of Korea and China would provide a better understanding of the current status of environmental pollution and ecosystem health. Graphical abstract: Image 1 Highlights: First reviewed ecological qualities of the Yellow Sea for the six tentative EcoQOs. EcoQOs for marine biodiversity and nutrient concentrations were met. EcoQOs for hypoxia and red-tide, pollutants, and marine litters were not meet. EcoQO for invasive species could not be judged due to insufficient meta-data. Further development and analyses of EcoQOs needed by joint efforts of Korea and China. Abstract : "Six tentative EcoQOs developed to assess current status of ecosystem health in the marine environments of the Yellow Sea with comparative review and analysis for selected ecosystem elements".